Self Care Practices among Hypertensive Patients with the View to Develop Informational Pamphlet - Priyanka Mohan Mali1, Mahesh B. Chendake2, Samir K. Choudhari3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Hypertension is condition approximately 25% affecting to adult population worldwide. Hypertension is said to be most common health problem all over the world. Prevalence of hypertension in India was 29.8%. Objective: study investigated the effectiveness of Informational Pamphlet on Self Care Practices among Hypertensive Patients. Method: One group pretest posttest design was used to conduct the study among hypertensive patients totally 60 patients were selected by Purposive sampling technique. Study conducted at Krishna hospital Karad. Data was collected by using structured questionnaire. Pre-test was conducted to assess the existing knowledge of self care practices regarding hypertension. Informational pamphlet was given to the patients then posttest level of knowledge was assessed by using same questionnaire. Results: Results of the present study shows that in the pretest most of the samples were having average knowledge (70%) regarding self care practices regarding hypertension and in postest majority (99.66%) were having good knowledge. The pretets mean was 12.08 and post-test mean was 18.78 and calculated t value was 6.70 found significant at the level of p<0.0001. Conclusion: Study concluded that information pamphlet was found effective to improve the Knowledge regarding self care practices among hypertensive patients.